1996
DOI: 10.1046/j.1365-2826.1996.04866.x
|View full text |Cite
|
Sign up to set email alerts
|

Corticotrophin‐Releasing Hormone Receptor Type 1: Generation and Characterization of Polyclonal Antipeptide Antibodies and their Localization in Pituitary Cells and Cortical Neurones in vitro

Abstract: Corticotrophin-releasing hormone (CRH) is a 41 amino acid neuropeptide which plays a major role in regulating the endocrine response to stress. CRH acts by first binding to specific receptors on the plasma membrane of target cells. A CRH receptor from a human corticotroph adenoma and rat brain has recently been cloned (CRH-R1). In this paper, we have chosen three different peptide sequences within the CRH-R1 molecule which bear no similarity to other members of this receptor subfamily (or indeed any known prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
21
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 32 publications
5
21
0
Order By: Relevance
“…Castro and colleagues reported a molecular mass for rat CRH R1 receptor in the pituitary ranging from 115-40 kDa (22). More recent studies have demonstrated sizes of 72 and 59 kDa in the mouse and rat (40).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Castro and colleagues reported a molecular mass for rat CRH R1 receptor in the pituitary ranging from 115-40 kDa (22). More recent studies have demonstrated sizes of 72 and 59 kDa in the mouse and rat (40).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, CRH R1 receptor protein levels decreased after the precocious elevation of plasma cortisol levels in fetuses before term. In the aforementioned studies, CRH R1 receptor protein with molecular masses of 40, 45, 59, 72, 99, 110, and 115 kDa (22,40) have been explained as potentially due to differences in glycosylation and alternative splicing and as a function of the quality of the membrane preparation (22,40). It is possible that the different molecular masses observed in the present study may be related to the ovine species, as no other studies have reported the molecular size of the CRH R1 in the sheep.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous reports describing molecular weights of CRFR1 from brain were controversial. By Western blot analysis using another polyclonal antibody against CRFR1 (Castro et al, 1996), 115-40 kDa forms of CRFR1 were found. On the basis of chemical cross-linking experiments, a 53 kDa form has 11.1 Ϯ 4.6 9.8 Ϯ 2.3 10.8 Ϯ 3.9 12.1 Ϯ 3.1 Statistically significant differences: *P Ͻ 0.05, **P Ͻ 0.01, ***P Ͻ 0.001 when compared to the corresponding value of the rat.…”
Section: Molecular Weights Of Crfr1 In Brain and Pituitary Tissuesmentioning
confidence: 99%
“…The predicted molecular weights (MW) of both CRHR1 and V1b receptors are 40-45 kilo Dalton (kDa). However, CRHR1 Western Blots show large molecular weight bands of 118 and 200 kDa in sheep anterior pituitaries (Green et al, 2000) and 115 kDa in rat anterior pituitaries (Castro et al, 1996). In addition, solubilization of radiolabeled CRH receptors in rat pituitary shows bands of 100-130 kDa in addition to a major band of 75 kDa (Grigoriadis and De Souza, 1988;Flores et al, 1990).…”
Section: Introductionmentioning
confidence: 99%